2019
DOI: 10.1002/jmrs.349
|View full text |Cite
|
Sign up to set email alerts
|

The changing landscape of head and neck cancer radiotherapy patients: is high‐risk, prolonged feeding tube use indicative of on‐treatment weight loss?

Abstract: IntroductionPrecision radiotherapy relies heavily on optimal weight management. Our group previously developed a risk stratification model for patients at risk of prolonged feeding tube (FT) intervention. The study objective was to assess on‐treatment weight loss according to stratified risk of prolonged FT use.MethodsOne hundred and one (n = 101) definitive head and neck radiotherapy patients were included in this study. Patients were stratified into high risk (HRi: T‐classification ≥ 3 with level 2 Nodal dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The authors concluded that T classification ≥ three and level two lymphadenopathy could potentially stratify patients into four risk groups for developing severe dysphagia requiring feeding tube use. The following risk groups of prolonged FT use were stratified: 1 In the next study, Anderson et al [63] analyzed 101 OPC patients undergoing RT. Patients were divided into high risk (HRi: T-classification ≥ three with level two Nodal disease), high-intermediate risk (HIRi: T-classification ≥ three without level two Nodes), and low-intermediate risk (LIRi: T-classification < three with level two Nodes) of prolonged feeding tube use.…”
Section: The Influence Of Hpv Status On Nutritional Status and Nutritmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that T classification ≥ three and level two lymphadenopathy could potentially stratify patients into four risk groups for developing severe dysphagia requiring feeding tube use. The following risk groups of prolonged FT use were stratified: 1 In the next study, Anderson et al [63] analyzed 101 OPC patients undergoing RT. Patients were divided into high risk (HRi: T-classification ≥ three with level two Nodal disease), high-intermediate risk (HIRi: T-classification ≥ three without level two Nodes), and low-intermediate risk (LIRi: T-classification < three with level two Nodes) of prolonged feeding tube use.…”
Section: The Influence Of Hpv Status On Nutritional Status and Nutritmentioning
confidence: 99%
“…In the next study, Anderson et al [ 63 ] analyzed 101 OPC patients undergoing RT. Patients were divided into high risk (HRi: T-classification ≥ three with level two Nodal disease), high-intermediate risk (HIRi: T-classification ≥ three without level two Nodes), and low-intermediate risk (LIRi: T-classification < three with level two Nodes) of prolonged feeding tube use.…”
Section: The Influence Of Hpv Status On Nutritional Status and Nutmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HPV-positive OPSCC are known to have better nutritional status at diagnosis than people with HPV-negative OPSCC [ 13 , 14 , 15 ]. Studies comparing the prevalence of malnutrition in HPV-positive and negative patients after treatment report similar, if not worse, nutritional outcomes for people who are HPV-positive compared to those who are HPV-negative [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that people who are HPV-positive are susceptible to a greater decline in nutritional status and potentially at greater risk of treatment-related malnutrition than people who are HPV-negative. Some studies attribute the comparatively worse nutritional outcomes in HPV-positive patients to lack of adherence to nutritional guidelines which leads to delayed feeding tube insertion and initiation of feeding [ 13 , 15 ]. Other studies suggest that patients with HPV-positive status are at greater risk of a decline in nutritional status due to experiencing worse treatment toxicities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%